PENGARUH IKLAN DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN VITACIMIN MELALUI BRAND TRUST - Caterine, Caterine; Tuti, Meylani (ESENSI: Jurnal Manajemen Bisnis, 2023)
The goal of this study was to ascertain how advertising and price perceptions affected consumers' decisions to buy Vitacimin. Statistically descriptive methods are used in the investigation. Using a purposive selection technique, 150 Vitacimin consumers were selected as the study's population. The SmartPLS 3 application was used to do data analysis using SEM. According to the study's findings, advertising and perceived price have a favorable and significant impact on consumer brand trust and purchasing behavior. Buying decisions are directly influenced by brand trust.